A case of Kallmann syndrome associated to a novel missense mutation of the FGFR1 gene - Scavone, Maria; Chiarello, Paola; Talarico, Valentina; Mascaro, Italia; Caglioti, Claudia; Galati, Maria Concetta; Raiola, Giuseppe (Acta Biomedica Atenei Parmensis, 2019)
Background: Loss-of-function mutations of fibroblast growth factor receptor 1 gene (FGFR1) have been reported so far. These mutations have been described in the extracellular domain, consisting of three Ig-like domains in the single transmembrane helix and in the intracellular region, containing a tyrosine kinase domain and cause about 10% of all cases of Kallmann syndrome. FRGR1 mutations could be associated with non reproductive phenotype such as cleft palate and dental agenesis and a wide spectrum of reproductive phenotype. Case Report: The patient, 17 years and 11 months old, was a Bulgarian male referred to our Pediatric Endocrinology Unit for pubertal failure and hyposmia. Clinical evaluation revealed a highpitched voice, gynecomastia and obesity. Hormonal study revealed hypogonadotropic hypogonadism. Molecular analysis, performed by Next Generation Sequencing and confirmed by Sanger sequencing, led to the identification of a novel and previously undescribed mutation c.1058 C>G (p. S353C) in heterozygous state on exon 8 of the FGFR1 gene. Conclusion: The novel mutation, that we found in a boy with Kallman syndrome, could destabilize the D3 immunoglobulin like receptor domain that is crucial for the FGF-FGFR interaction. (www.actabiomedica.it)